Arthrobacter enclensis sp. nov., isolated from sediment sample - Dastager, Syed Gulam; Qin, Liu; Tang, Shan-Kun; Krishnamurthi, Srinivasan; Lee, Jae-Chan; Li, Wen-Jun (Archives of Microbiology, 2014)
A novel bacterial strain designated as NIO-1008(T) was isolated from marine sediments sample in Chorao Island India. Cells of the strains were gram positive and non-motile, displayed a rod-coccus life cycle and formed cream to light grey colonies on nutrient agar. Strain NIO-1008(T) had the chemotaxonomic markers that were consistent for classification in the genus Arthrobacter, i.e. MK-9(H-2) (50.3 %), as the major menaquinone, and the minor amount of MK-7 (H-2-27.5 %), MK-8 (H-4-11.6 %) and MK-8 (H-2-10.4 %). anteiso-C-15:0, iso-C-15:0, iso-C-16:0 and C-15:0 were the predominant fatty acids. Galactose, glucose and rhamnose are the cell-wall sugars, and DNA G+C content was 61.3 mol%. Phylogenetic analysis, based on 16S rRNA gene sequencing, showed that the strains were most similar to Arthrobacter equi IMMIB L-1606(T), Arthrobacter chlorophenolicus DSM 12829(T), Arthrobacter defluvii KCTC 19209(T) and Arthrobacter niigatensis CCTCC AB 206012(T) with 98.5, 98.4, 98.0 and 97.8 %, respectively, and formed a separate lineage. Combined phenotypic data and DNA-DNA hybridization data supported the conclusion that strains NIO-1008(T) represent a novel species within the genus Arthrobacter, for which the name Arthrobacter enclensis sp. nov., is proposed. The type strain is NIO-1008(T) = (NCIM 5488(T) = DSM 25279(T)).
Keywords: Arthrobacter; Chorao Island; Marine sediment; Polyphasic

Arthrobacter enclensis sp. nov., isolated from sediment sample (vol 196, pg 775, 2014) - Dastager, Syed Gulam; Liu, Qing; Tang, Shan-Kun; Krishnamurthi, Srinivasan; Lee, Jae-Chan; Li, Wen-Jun (Archives of Microbiology, 2014)

Bacillus enclensis sp nov., isolated from sediment sample - Dastager, Syed Gulam; Mawlankar, Rahul R.; Tang, Shan-Kun; Srinivasan, Krishnamurthi; Ramana, V. Venkata; Shouche, Yogesh S. (Antonie Van Leeuwenhoek International Journal of General and Molecular Microbiology, 2014)
A novel bacterial strain, designated SGD-1123(T) was isolated from Chorao Island, in Goa Province, India. The strain was found to be able to grow at 15-42 A degrees C, pH 5-12 and 0-12 % (w/v) NaCl. The whole cell hydrolysates were found to contain meso-diaminopimelic acid, galactose and arabinose. The major fatty acids were identified as iso-C-15:0 and anteiso-C-15:0, MK-7 was identified as the predominant menaquinone and the predominant polar lipids were identified as diphosphatidylglycerol, phosphatidylglycerol, phosphatidylethanolamine and an unidentified aminolipid. The genomic DNA G+C content was determined to be 44.6 mol%. Phylogenetic analysis based on 16S rRNA gene sequences placed the isolate within the genus Bacillus and further revealed that strain SGD-1123(T) had highest sequence similarity with Bacillus aquimaris, and forms a separate clade with its closest relatives i.e. B. aquimaris, Bacillus vietnamensis and Bacillus marisflavi, with which it shares 94.5, 94.1 and 94.1 % similarity respectively. The phylogenetic, chemotaxonomic and phenotypic analyses indicated that strain SGD-1123(T) represents a novel species within the genus Bacillus, for which the name Bacillus enclensis is proposed. The type strain is SGD-1123(T) (NCIM 5450(T)=CCTCC AB 2011125(T)).
Keywords: Bacillus sp; Marine sediment; Polyphasic

Domibacillus enclensis sp nov., isolated from marine sediment, and emended description of the genus domibacillus - Sonalkar, Vidya V.; Mawlankar, Rahul R.; Krishnamurthi, Srinivasan; Tang, Shan-Kun; Dastager, Syed Gulam (International Journal of Systematic and Evolutionary Microbiology, 2014)
A novel red-pigmented bacterial strain, designated NIO-1016(T), was isolated from a sediment sample from Chorao Island, India and was investigated by a polyphasic taxonomic approach. The strain was Gram-reaction-positive, strictly aerobic, motile and catalase-positive and produced spherical to slightly ellipsoidal endospores with subterminal position on swollen sporangia. The genomic DNA G+C content was 46.9 molok. The major fatty acids were anteiso-C-15:0, anteiso-C-17:0, iSO-C-15:0 and C-16:0. The predominant quinones were MK-6 (89.3 %) and MK-7 (8.7 %). The polar lipids consisted of diphosphatidylglycerol, phosphatidylglycerol, and an unidentified phospholipid. meso-Diaminopimelic acid (type My) was present in the cell-wall peptidoglycan and the major whole-cell sugars were glucose and ribose. The closest phylogenetic neighbours were identified as Domibacillus robiginosus DSM 25058(T) (98.0% similarity) and Domibacillus indicus DSM 28032(T) (97.2% similarity), other species of the genus Bacillus displayed below 96% similarity. Phylogenetic, physiological, biochemical and morphological differences between strain NI0-1016(T) and its closest neighbours indicate that this strain represents a novel species in the genus Domibacillus in the family Bacillaceae for which the name Domibacillus enclensis sp. nov. is proposed with the type species N10-1016(T) (=DSM 25145(T)=NCIM 5462(T)=CCTCC AB 2011121(T)).

Fictibacillus enclensis sp nov., isolated from marine sediment - Dastager, Syed Gulam; Mawlankar, Rahul R.; Srinivasan, Krishnamurthi; Tang, Shan-Kun; Lee, Jae-Chan; Ramana, V. Venkata; Shouche, Yogesh S. (Antonie Van Leeuwenhoek International Journal of General and Molecular Microbiology, 2014)
A novel Gram-positive strain, designated NIO-1003(T), was isolated from a marine sediment sample collected from the Chorao Island, Goa Provence, India. Strain NIO-1003(T) was found to be strictly aerobic, motile, endospore-forming rods. Phylogenetic analysis based on 16S rRNA gene sequences indicated that strain NIO-1003(T) belongs to the genus Fictibacillus and to be most closely related to Fictibacillus rigui KCTC 13278(T), Fictibacillus solisalsi KCTC 13181(T) and Fictibacillus barbaricus DSM 14730(T) with 98.2, 98.0 and 97.2 % similarity and 25, 28, 39 nucleotide differences respectively. Strain NIO-1003(T) was characterized by having cell-wall peptidoglycan based on meso-diaminopimelic acid and MK-7 as the predominant menaquinone. The polar lipid profile exhibited the major compounds diphosphatidylglycerol, phosphatidylglycerol and phosphatidylethanolamine. In addition, minor amounts of an aminophospholipid were detected. The major fatty acids were identified as ai-C-15:0, iso-C-15:0, ai-C-17:0 and C-16:0, supporting the grouping of strain NIO-1003(T) into the family Bacillaceae. The DNA G+C content of strain NIO-1003(T) was determined to be 42.6 mol%. On the basis of phenotypic properties, phylogeny and DNA-DNA hybridisation analysis, strain NIO-1003(T) is considered to represent a novel species of the genus Fictibacillus for which the name Fictibacillus enclensis sp. nov. is proposed. The type strain is NIO-1003(T) (= NCIM 5458(T) = DSM 25142(T)).
Keywords: Chorao Island; Fictibacillus sp.; Polyphasic taxonomy

Kocuria indica sp nov., isolated from a sediment sample - Dastager, Syed Gulam; Tang, Shan-Kun; Srinivasan, Krishnamurthi; Lee, Jae-Chan; Li, Wen-Jun (International Journal of Systematic and Evolutionary Microbiology, 2014)
An actinobacterial strain was isolated from a sediment sample from Chorao Island, in Goa province, India, and subjected to a taxonomic investigation. The isolate, designated NIO-1021(T), was a Gram-stain positive, aerobic, non-motile and coccoid. Strain NIO-1021(T) was identified as a member of the genus Kocuria by a polyphasic approach. Strain NIO-1021(T) could be differentiated from other members of the genus Kocuria on the basis of physiology and 16S rRNA gene sequence analysis. The 16S rRNA gene sequence similarity of strain NIO-1021(T) to the most closely related species, Kocuria marina KCTC 9943(T), was 98.6% with 19 nt differences). Furthermore, DNA-DNA hybridization analysis revealed that the novel strain had lower relatedness with the type strains of other members of the genus Kocuria. The strain formed a monophyletic clade with K. marina with 100% bootstrap values. The major phospholipids were phosphatidylglycerol, diphosphatidylglycerol and two unidentified lipids. The predominant menaquinone was MK-7(H-2). The major fatty acids were anteiso-C-15:0, iso-C-(16:0) and anteiso-C-17:0. The DNA G+C content of strain NIO-1021(T) was 60.5 mol%. Chemotaxonomic and phylogenetic properties of the strain were consistent with its classification as representing a member of the genus Kocuria. On the basis of phenotypic, chemotypic and molecular characteristics, strain NIO-1021(T) is considered to represent a novel species of the genus Kocuria, for which the name Kocuria indica sp. nov. is proposed, with strain NIO-1021(T) (=NCIM 5455(T)=DSM 25126(T)=CCTCC AA 209050(T)) as the type strain.

Rhodococcus enclensis sp nov., a novel member of the genus rhodococcus - Dastager, Syed Gulam; Mawlankar, Rahul R.; Tang, Shan-Kun; Krishnamurthi, Srinivasan; Ramana, V. Venkata; Joseph, Neeta; Shouche, Yogesh S. (International Journal of Systematic and Evolutionary Microbiology, 2014)
A novel actinobacterial strain, designated, NIO-1009(T), was isolated from a marine sediment sample collected from Chorao Island, Goa, India. Phylogenetic analysis comparisons based on 16S rRNA gene sequences between strain MO-1009(T) and other members of the genus Rhodococcus revealed that strain NI0-1009(T) had the closest sequence similarity to Rhodococcus kroppenstedtii DSM 44908(T) and Rhodococcus corynebacterioides DSM 20151(T) with 99.2 and 99.1%, respectively. Furthermore, DNA-DNA hybridization results showed that R. kroppenstedtii DSM 44908(T) and R. corynebacterioides DSM 20151(T) were 39.5 (3.0%) and 41.7 (2.0%) with strain NIO-1009(T), respectively, which were well below the 70% limit for any novel species proposal. Phylogenetically strain NIO-1009(T) forms a stable clade with and R. kroppenstedtii DSM 44908(T) and R. corynebacterioides DSM 201511 with 100% bootstrap values. Strain NI-1009(T) contained meso-diaminopimelic acid as the diagnostic diamino acid and galactose and arabinose as the cell wall sugars. The major fatty acids were C-16:0, C-18:1 omega 9c, C-16:1(omega 6C and/or omega 7c) and 10-methyl C-18:0. The only menaquinone detected was MK-8(H-2), while the major polar lipids were diphosphatidylglycerol, phosphatidylethanolamine, phosphatidylglycerol, phosphatidylinositol, phosphatidylinositol mannoside and one unknown phospholipid. The G + C content of the genomic DNA was 66.9 molok. The phenotypic and genotypic data showed that strain NIO-1009(T) warrants recognition as a novel species of the genus Rhodococcus for which the name Rhodococcus enclensis sp. nov., is proposed; the type strain is NIO-1009(T) (=NCIM 5452(T)=DSM 45688(T)).

Exiguobacterium enclense sp nov., isolated from sediment - Dastager, Syed Gulam; Mawlankar, Rahul R.; Sonalkar, Vidya V.; Thorat, Meghana N.; Mual, Poonam; Verma, Ashish; Krishnamurthi, Srinivasan; Tang, Shan-Kun; Li, Wen-Jun (International Journal of Systematic and Evolutionary Microbiology, 2015)
A Gram-stain-positive bacterium, designated strain NIO-1109(T), was isolated from a marine sediment sample from Chorao Island, Goa, India. Phenotypic and chemotaxonomic characteristics and data from phylogenetic analysis based on 16S rRNA gene sequences indicated that strain NIO-1109(T) was related to the genus Exiguobacterium. Strain NIO-1109(T) exhibited >98.0% 16S rRNA gene sequence similarity with respect to Exiguobacterium indicum HHS 31(T) (99.5%) and Exiguobacterium acetylicum NCIMB 9889(T) (99.1 %); the type strains of other species showed <98% similarity. Levels of DNA DNA relatedness between strain NIO-1109(T) and E. acetylicum DSM 20416(T) and E indicum LMG 23471(T) were less than 70% (33.0 +/- 2.0 and 37 +/- 32%, respectively). Strain NIO-1109(T) also differed from these two closely related species in a number of phenotypic traits. Based on phenotypic, chemotaxonomic and phylogenetic data, strain NIO-1109(T) is considered to represent a novel species of the genus Exiguobacterium, for which the name Exiguobacterium enclense sp. nov. is proposed. The type strain is NIO-1109(T) (=NCIM 5457(T)= DSM 25128(T)=CCTCC AB 2011124(T)).

Kocuria indica sp. nov., isolated from a sediment sample (vol 64, pg 869, 2014) - Dastager, Syed G.; Tang, Shan-Kun; Srinivasan, Krishnamurthi; Lee, Jae-Chan; Li, Wen-Jun (International Journal of Systematic and Evolutionary Microbiology, 2017)